Plasma Homocysteine Levels And Efficacy Of Vitamin Supplementation Among Patients With Atherosclerosis – A Spectral And Clinical Follow Up - A. BRIGHT; T. S. RENUGA DEVI; S. GUNASEKARAN (International Journal of Pharma and Bio Sciences, 2011)
Homocysteine is an amino acid, which is metabolized either by the remethylation pathway to methionine or the trans-sulfuration pathway to cysteine. The former pathway is dependent on the proper functioning of the enzymes methionine synthetase and methylene tetrahydrofolate reductase as well as adequate blood levels of vitamin B12 and folic acid. The later pathway is dependent on the enzyme cystathionine beta synthetase and adequate blood levels of pyridoxine (vitamin B6). A genetic defect in the enzyme or a dietary deficiency of the vitamins involved in the metabolism of homocysteine can result in hyperhomocysteinemia. It is a strong, graded, independent risk factor for stroke, myocardial infarction and other vascular events. The present work aims at the application of Fourier-Transform Infrared Spectroscopy for the analysis of blood plasma of patients with atherosclerosis inorder to detect spectral parameters which might serve as biomarker for identifying and detecting homocysteine levels. The analysis led to the identification of specific modes of vibration pertaining to homocysteine in blood plasma. The absorbance values at these specific modes of vibration were significantly increased for the diseased when compared to healthy individuals. For five patients, before the initiation of vitamin supplements along with their regular medication the FTIR spectra of the blood plasma was recorded and their homocysteine levels were clinically tested. They were orally administered a daily dosage of folic acid(5 mg), vitamin B12(250mcg) and vitamin B6(25mg) supplements for a period of two months. Efficacy of these vitamin supplements were analyzed both clinically and spectroscopically at the end of the first and the second month and also the homocysteine levels were clinically tested. The absorption values of the specific modes of vibration pertaining to homocysteine of both pre and post-treatment spectra were noted and the percentage of efficacy of the multivitamins was calculated. The spectral and clinical investigation showed that the addition of these vitamins can markedly reduce the homocysteine levels in blood plasma.